An Easy‐to‐Fabricate Hydrogel Platform with Tunable Stiffness and Cell Anchorage: Validation of Its Feasibility in Modulating Sonic Hedgehog Signaling Pathway Physically. Issue 4 (11th March 2020) - Yu, Tingting; Hu, Ke; Xu, Qiufan; Xu, Xueqin; Du, Chunyue; Zhao, Yinyi; Yan, Sen; Wang, Wei; Tang, Shijia; Yue, Shen; Zhang, Xiya; Wang, Danlei; et al.
Abstract: The biophysical factors of microenvironments have increasingly been recognized as playing key roles in driving cell functions along with biochemical cues. However, current synthetic extracellular matrix materials with tunable biophysical properties are both costly and technically complicated to prepare, therefore limiting their application in the molecular biology field. Herein, an interpenetration hydrogel group with gradient stiffness and cell anchor points is developed, and the matrix stiffness and adhesion property functions as key regulators to determine the final output of Sonic Hedgehog (Shh) signaling is reported. Specifically, it is shown that the spreading areas of mouse embryonic fibroblasts are mainly regulated by stiffness of the matrix. The Shh‐induced Gli1 expression also increases with the cell spreading area. Finally, this work shows that b1‐integrin and focal adhesion kinase, respectively, act as sensors of matrix stiffness and adhesion properties, demonstrating the significance of the precise regulation of Shh signaling by cellular microenvironments. These results demonstrate the feasibility of using this hydrogel platform to study the impact of biophysical changes of the microenvironment on particular cellular signal pathways, and can potentially be applied in low‐cost, high throughput screening of signal pathways which are responsive to the biophysical changes of microenvironments. Abstract : An interpenetration hydrogel group with gradient stiffness and cell anchor points are prepared. The matrix stiffness and adhesion property functions serve as key regulators to determine the final output of Sonic Hedgehog signaling. These results demonstrate the feasibility of using this low‐cost hydrogel platform to study the impact of biophysical changes of microenvironment on particular cellular signal pathways.